2018
DOI: 10.1111/codi.14057
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ovarian metastases on survival in patients treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for peritoneal malignancy originating from appendiceal and colorectal cancer

Abstract: Women with ovarian metastases from low-grade appendiceal tumours or colorectal cancer treated with CRS and HIPEC have similar survival rates to patients without ovarian metastases. Long-term survival and cure is feasible in patients amenable to complete tumour removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…We found that 41.8% of female PMP patients had resection of both ovaries before being referred for CRS þ HIPEC. Bignell et al [29] found similar results with 36.3% of women having both ovaries resected at index surgery (prereferral).…”
Section: Umbilicusmentioning
confidence: 66%
“…We found that 41.8% of female PMP patients had resection of both ovaries before being referred for CRS þ HIPEC. Bignell et al [29] found similar results with 36.3% of women having both ovaries resected at index surgery (prereferral).…”
Section: Umbilicusmentioning
confidence: 66%
“…Since ovarian lining and peritoneal lining are derived from the same embryological origins, the same results can be extrapolated to cases of ovarian metastases. And this has been confirmed in a study comparing PC patients with ovarian metastases undergoing CRS+HIPEC to PC patients without ovarian metastases undergoing CRS+HIPEC, wherein both groups showed similar survival rates [28]. Even the studies addressing CRS+HIPEC have stressed the need and significance of optimal cytoreduction to have a meaningful improvement in outcomes [29][30][31] while the role of HIPEC is still debated.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to traditional belief, the presence of ovarian metastases of colorectal cancer origin is no longer considered to be associated with decreased survival outcomes, provided that a complete cytoreduction is achieved and combined with HIPEC [37,38].…”
Section: Cytoreductive Surgery: "Complete Cytoreductive (Cc)" Scoring Systemmentioning
confidence: 97%